Struktur dan Pembentukan Kata dalam Bahasa Indonesia - Nubaisy Khair Ma’ruf; Muhammad Rifky Ramadhana; Agung Pranoto Kadiatmaja (INDO PUBLISHING, 2026)
This study examines the structure and mechanisms of word formation in Indonesian, emphasizing morphological phenomena such as affixation, reduplication, and composition. The background is rooted in the complexity of word formation processes in Indonesian that require structured academic study. The aim of this study is to describe the types of word structures and productive word formation processes in Indonesian. The method applied is descriptive qualitative with data collection through literature study and document analysis of primary linguistic sources. The findings show that words in Indonesian are divided into basic words and derived words, and the word formation process is dominated by affixation, including prefixes (me-, ber-, di-, pe-, ter-, ke-), suffixes (-kan, -an, -i), and confixes (me-…-kan, me-…-i, ber-…-an). Reduplication and composition also play an important role in expanding vocabulary. The research findings confirm that morphological processes in Indonesian are productive and regular, in line with the theoretical frameworks of Chaer (2008) and Kridalaksana (2009). This research deepens our understanding of Indonesian morphology and provides pedagogical implications for language teaching and learning.